Public Zen, personal Zen : a Buddhist introduction - Hershock, Peter D. (Lanham : Rowman & Littlefield, 2014)
This deeply informed book introduces the basic teachings and practices of Buddhism and their spread across Asia. Peter D. Hershock explores the history of the enduring Japanese tradition of Zen-from its beginnings as a form of Buddhist thought and practice imported from China to its reinvention in medieval Japan as a force for religious, political, and cultural change to its role in Japan's embrace of modernity. He deftly blends historical detail with the felt experiences of Zen practitioners grappling with the meanings of human suffering, personal freedom, and the integration of s.
Zen Origins -- Public Zen -- Personal Zen.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Zen Buddhism -- History; RELIGION -- Comparative Religion; Zen Buddhism; Electronic books; History